Explaining the rise of Populism in Hungary since 2010: The analytic power of anti-establishment theory - Khuzwayo, Siyabonga Robert (Department of Political Studies, 2025)
There is a great debate regarding the causes of populism. Most research done on the causes of populism uses the comparative method. However, a single case study allows the researcher to uncover underlying factors fueling populism in a specific country. This dissertation investigates the factors that explain the rise of populism in Hungary since 2010 to interrogate the prominent ‘anti-establishment' theory with the hope of identifying ways to deepen this theory's analytical power. The research reveals that the anti-establishment theory helps us to understand the rise of populism in Hungary. However, it is insufficient because it omits critical factors that contributed to the emergence of populism in the case under investigation. These include socio-cultural and socio-economic factors, charismatic leadership, liberal democracy's lack of mechanisms to prevent an outbreak of populism, and the effects of state capture. The anti-establishment theory can be more analytically robust by incorporating these omitted factors.